Urban Sufism from Exclusiveness to Inclusiveness: A Metaphysical Perspective - Syukri Al Fauzi Harlis Yurnalis; Endrika Widdia Putri; Arrasyid Arrasyid (Teosofia: Indonesian Journal of Islamic Mysticism, 2022)
Every human being looks for sa'āda (happiness) in this world. However, this paradigm has recently shifted. It is now emerging amid urban communities, especially among Indonesian Muslims searching for spiritual values. This qualitative study aims to answer the above argument using a sufistic approach by analysing human nature and the nature of happiness, which are the factors supporting the birth of urban sufism. Besides, it also uses a phenomenological approach to see urban sufism, especially in the cities of Jakarta and Bandung, as an example of the development of urban sufism. This study found that the paradigm shift was caused by the revival of human awareness that the spiritual aspect is a source of true happiness within human beings.Contribution: This article provides a rational reason to show that sufism is not only for certain circles but is universal and needed for every human being, especially for the conditions of this era. Every human needs sufism as it is a metaphysical human element consisting of Nūr Muḥammadiyy and Adamiyy